Traumatic brain injury increases levels of miR‐21 in extracellular vesicles: implications for neuroinflammation - Harrison, Emily B.; Hochfelder, Colleen G.; Lamberty, Benjamin G.; Meays, Brittney M.; Morsey, Brenda M.; Kelso, Matthew L.; Fox, Howard S.; Yelamanchili, Sowmya V. (FEBS open bio, 2016)
Traumatic brain injury (TBI) is an important health concern and effective treatment strategies remain elusive. Understanding the complex multicellular response to TBI may provide new avenues for intervention. In the context of TBI, cell–cell communication is critical. One relatively unexplored form of cell–cell communication in TBI is extracellular vesicles (EVs). These membrane‐bound vesicles can carry many different types of cargo between cells. Recently, miRNA in EVs have been shown to mediate neuroinflammation and neuronal injury. To explore the role of EV‐associated miRNA in TBI, we isolated EVs from the brain of injured mice and controls, purified RNA from brain EVs, and performed miRNA sequencing. We found that the expression of miR‐212 decreased, while miR‐21, miR‐146, miR‐7a, and miR‐7b were significantly increased with injury, with miR‐21 showing the largest change between conditions. The expression of miR‐21 in the brain was primarily localized to neurons near the lesion site. Interestingly, adjacent to these miR‐21‐expressing neurons were activated microglia. The concurrent increase in miR‐21 in EVs with the elevation of miR‐21 in neurons, suggests that miR‐21 is secreted from neurons as potential EV cargo. Thus, this study reveals a new potential mechanism of cell–cell communication not previously described in TBI. Traumatic brain injury induced global changes in the miRNA content of brain‐derived extracellular vesicles (EVs), with expression of miR‐21 showing the largest increase. Furthermore, miR‐21 showed neuronal expression in the lesion boundary, suggesting that neurons are the major source of extracellular miR‐21. Overall, these findings indicate that miR‐21 may play a crucial role in cell–cell communication after brain injury.